The Primary Cilium as a Novel Extracellular Sensor in Bone - Hoey, David A.; Chen, Julia C.; Jacobs, Christopher R. (Frontiers in Endocrinology, 2012)
Mechanically induced adaptation of bone is required to maintain a healthy skeleton and defects in this process can lead to dramatic changes in bone mass, resulting in bone diseases such as osteoporosis. Therefore, understanding how this process occurs could yield novel therapeutics to treat diseases of excessive bone loss or formation. Over the past decade the primary cilium has emerged as a novel extracellular sensor in bone, being required to transduce changes in the extracellular mechanical environment into biochemical responses regulating bone adaptation. In this review, we introduce the primary cilium as a novel extracellular sensor in bone; discuss the in vitro and in vivo findings of primary cilia based sensing in bone; explore the role of the primary cilium in regulating stem cell osteogenic fate commitment and finish with future directions of research and possible development of cilia targeting therapeutics to treat bone diseases.